Tendances de l'Art en France 1968-1978/9 - 1. - Pleynet, Marcelin; Pagé, Suzanne (Paris : ARC Musée d'Art Moderne de la Ville de Paris, 1979)
Barré, Martin ; Bishop, James ; Debré, Olivier ; Degottex, Jean ; Francis, Sam ; Hantaï, Simon ; Mitchell, Joan ; Reigl, Judit ; Soulages, Pierre ; Audat, Jean-Baptiste ; Bioulès, Vincent ; Bonnefoi, Christian ; Buraglio, Pierre ; Cane, Louis ; Devade, Marc ; etc.
Tendances de l'Art en France 1968-1978/9 - 1, ARC Musée d'Art Moderne de la Ville de Paris, Paris, 13 septembre - 21 octobre 1979
boek
Keywords: Frankrijk